(untitled) (Economic and Political Thought, 2016)
The article deals with the intercultural relations between Poland and Germany within the European Union. The first part of the article is devoted to the analysis of cultural similarities and differences between the societies of the two countries. The second part of the article, on the other hand, the proper one from the point of view of its title, presents the issue of intercultural communication between Poland and Germany exemplified by three case studies: Polish and German business culture, Polish and German local border traffic and intercultural relations between Polish and German students at European University Viadrina in Frankfurt (Oder).